2020
DOI: 10.18844/prosoc.v7i1.4867
|View full text |Cite
|
Sign up to set email alerts
|

Current trends in education technologies research worldwide: Meta-analysis of studies between 2015 and 2020

Abstract: The interaction between education and technology affects the developments occurring in two areas and the developments in education increase the speed of technological developments. Educational technology is the functionalisation of the scientific knowledge produced in educational sciences and its application in practice. In this research, the content analysis of the studies conducted in Turkey and abroad in the last 5 years, in order to determine the current trends in educational technology researches,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 3 publications
1
12
0
Order By: Relevance
“…In the process of organizing and conducting a diagnostic procedure, it is necessary to implement the principle of dialogue, based on the notion that dialogue is possible with a person only as a free individual, who are able to evaluate himself, his life, and the circumstances of this life. The principle implies equal interaction of participants in the diagnostic process (Yildiz, Alkan & Cengel, 2020). It implies the possibility of obtaining timely feedback and making corrections in the interpretation of results.…”
Section: Discussionmentioning
confidence: 99%
“…In the process of organizing and conducting a diagnostic procedure, it is necessary to implement the principle of dialogue, based on the notion that dialogue is possible with a person only as a free individual, who are able to evaluate himself, his life, and the circumstances of this life. The principle implies equal interaction of participants in the diagnostic process (Yildiz, Alkan & Cengel, 2020). It implies the possibility of obtaining timely feedback and making corrections in the interpretation of results.…”
Section: Discussionmentioning
confidence: 99%
“…Students positively reported the effectiveness of online learning during the pandemic, wherein covid cases are not stable. Findings revealed that educational technology is appropriate in teaching and learning (Yildiz, 2020).…”
Section: Review Of Literaturementioning
confidence: 98%
“…Tool (1):-An online questionnaire was used and developed to collect data pertinent to this study which was designed by the researchers after literature search and based on the most recently available information from the (World Health Organization, 2020, 2020; Yildiz, et al, 2020;and Rajab et al, 2020). It included (yes/no, multiple-choice, and openended questions), which covered the study's objectives.…”
Section: Tools For Data Collectionmentioning
confidence: 99%